Vulnerability of Inuit Food Systems to Climate Change and Socio-Economic Changes - Parker, C; Pearce, T (ArcticNet Inc., 2013)
Food security exists when individuals and households have reliable access to safe, nutritionally adequate, and culturally acceptable foods in a manner that maintains human dignity (Van Esterik 1999). Food security and health are closely linked with those who are food insecure more likely to suff er from compromised health status. The highest incidence of food insecurity in Canada has been reported in Nunavut where 56% of the Inuit population is classed as food-insecure (Ledrou and Gervais 2005). Inuit food systems combine store foods and country foods derived from subsistence hunting and fi shing. Th ere is an emerging body of research identifying the relationships between climate change and food security, including among Inuit in the Canadian Arctic. The high reliance of some Inuit households on country foods makes Inuit food systems sensitive to changes in the weather, sea ice, land, and wildlife associated with climate change, which aff ects access (e.g. travel to hunting grounds), availability (e.g. location of wildlife), and quality (e.g. health of wildlife) of some species of wildlife important for subsistence. These challenges are further compounded by other stresses to the food system including access to income to purchase hunting equipment and supplies or to purchase store bought foods, access to cold storage, confl icts between wage employment and hunting opportunities, and the erosion of some traditional knowledge and skills important for safe and successful hunting among some younger generation Inuit. Less is known about how climate and non-climate stressors interact to aff ect food security and the capacity of individuals and households to adapt. The proposed research will work with community members in the Inuit hamlet of Ulukhaktok, Northwest Territories to examine the vulnerability of an Inuit food system to climate and socio-economic changes and adaptation options. Th e objectives are: (1) characterize key elements of the community food system with particular attention to traditional food attributes (e.g. food preference); (2) apply a framework for vulnerability assessment to examine how multiple stresses, climate and non-climate related, aff ect access, availability, quality and storage of food; and (3) identify and describe opportunities and barriers to enhancing food security. Data will be collected using ethnographic research techniques including food system surveys, semi-structured interviews, and participant observation. Th is data will be analyzed together with existing knowledge of the biophysical processes of climate change relevant to food security in the region. Th e research is expected to contribute to the growing body of knowledge examining the relationships between food security and climate change, and provide new insights into the socio-cultural dimensions of Inuit food security. Th e research is part of ArcticNet Project 1.1 Community Adaptation and IK-ADAPT (Inuit Traditional Knowledge for Adaptation to the Health Eff ects of Climate Change) supported by CIHR.